ANALISIS IMPLEMENTASI GERAKAN LITERASI SEKOLAH DALAM PEMBELAJARAN SOSIOLOGI DI SMA GEMBALA BAIK PONTIANAK - Provetangelina, Fortunata; Rustiyarso, Rustiyarso; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe title of this thesis is An Analysis on the Implementation of Gerakan Literasi Sekolah in Sociology Learning in SMA Gembala Baik Pontianak. The general problem in this research is "How was the implementation of Gerakan Literasi Sekolah in Sociology learning in SMA Gembala Baik Pontianak? The specific problems are (1) How was the Implementation of Gerakan Literasi Sekolah on the development phase in Sociology learning in SMA Gembala Baik Pontianak? (2) How was the implementation of Gerakan Literasi Sekolah on the learning phase in Sociology learning in SMA Gembala Baik Pontianak? The research approach that is used is qualitative research. The techniques of data collection used are observation technique, interview, and document study. The tools of data collection are observation guidelines, interview guidelines, field note, and documentation. The result of this research showed that (1) On the implementation of Gerakan Literasi Sekolah on the development phase in Sociology learning in SMA Gembala Baik Pontianak, the activity that has been implemented are reading activity for 15 minutes, the Sociology teacher was being the model in the reading activity, and there was a follow-through activity in giving feedback on the reading. (2) On the implementation of Gerakan Literasi Sekolah on the learning phase in Sociology learning in SMA Gembala Baik Pontianak, reading activity has been entrenched and has become a need in the learning process in the classroom, the reading strategies that were done in the learning are silent reading and reading aloud, also there was an academic requirement in the form of follow-through activity to give feedbacks orally or in writing.Keywords: GLS, Implementation, SMA